Relocating Lives in the 'Britain of the South': The Influence of Emigrant Advice Manuals on the Public Writings of Nineteenth-Century Female Emigrants. Issue 4 (2nd October 2017) - Coleman, Jenny
ABSTRACT: Throughout the nineteenth century, emigration from England to the colonies was actively promoted through promotional literature (known as 'booster' literature) in the form of books, pamphlets, newspaper and journal articles, scientific and ethnographic works, lectures and advertisements. The emigration companies and agents were undoubtedly self-promoting propagandists; nevertheless, the emigrant advice literature was highly influential. This article considers the ways in which nineteenth-century female immigrants to New Zealand drew on booster literature in their public writings. The specific focus is on three selected pieces of life writing, each of which mirrors key features of emigrant advice literature: a letter describing life in New Zealand from an unnamed settler's wife in 1852; an essay titled 'A Few Last Words About Auckland', written as an appendix to a loosely autobiographical novel published in 1882; and a booklet titled ' Taken In'; Being, A Sketch of New Zealand Life published in 1887. They are analysed through social historian Miles Fairburn's thematic frame of New Zealand as a country of natural abundance that provided ample opportunities for labouring people to achieve independence, and a society which naturally created a high level of order and guaranteed middle-class people freedom from status anxiety through a simple life.